PENGEMBANGAN MODAL SOSIAL MAHASISWA UNIVERSITAS PANCASAKTI MAKASSAR - Ismail Ismail; Rahmatul Hidayat (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Hasanuddin, 2020)
This study aims to explore the potential for social capital of students at Pancasakti University Makassar, from the aspects of increasing trust, the ability of student social interaction, the reciprocal ability of students to develop and increase the capacity and abilities of students. This study uses a phenomenological research method with a qualitative approach. Data collection techniques of this research is done by interviews, observation, review of documents. The research data were analyzed using the stages of data reduction, data presentation, and drawing conclusions. The results show that the level trust of mutual trust between bureaucratic staff, lecturers and students has not been well developed so that there is still a slight gap in campus. Student trust in campus institutions is still considered lacking because many students think that the campus has not been transparent about the information needed by students, both academic and non-academic information such as scholarship information that can be accessed by the students themselves. Social interaction that occurs at the campus is considered not optimal because there are several high-ranking officials and lecturers who have activities or activities outside the campus, but overall the social interactions that are built on campus are considered good. Reciprocal has been built well because students and lecturers have mingled with each other during their grace period in the campus environment and lecturers, besides that their level of acceptance on campus is very good and open.